Förändringar i vinterklimat och samhällets beredskap : En fallstudie över kommunalt klimatanpassningsarbete för framtida vinterklimat - Malmheim, Adam; Kant, Gabriel (Blekinge Tekniska Högskola, Institutionen för fysisk planering, 2024)
The climate is changing, and winters are expected to receive increasingly more precipitation in large parts of Sweden. Climate change brings significant risks and challenges, such as an increased risk of flooding, erosion, landslides, and avalanches. Through a case study of four Swedish municipalities: Uddevalla, Karlstad, Gällivare, and Kiruna, a document study examines how these municipalities' climate adaptation efforts related to changing winter climates are being conducted. The results of the case study are presented through quantitative tables and qualitative discussions. Specific points have been selected for the quantitative tables, which have been used to grade the municipalities' climate adaptation efforts for future winter climates. The study has shown that the four municipalities studied are conducting climate adaptation efforts related to a changing winter climate. The extent to which the municipalities carry out climate adaptation work varies. Winter climate changes are more pronounced in southern Sweden than in the north. This is reflected in the municipalities' climate adaptation efforts. Uddevalla and Karlstad municipalities have made more progress in their climate adaptation efforts and have been working on it for several years. Gällivare and Kiruna municipalities experience fewer climate changes during the winter, and therefore their climate adaptation efforts are smaller and not as extensive and concrete as those in Uddevalla and Karlstad municipalities.